The Challenges and Prospects of ICTs in Crime Prevention and Management in Nigeria: A Review of CCTV Cameras in Abuja - Nte, Ngboawaji Daniel; Gande, Graham; Uzorka, Michael (IJCLS (Indonesian Journal of Criminal Law Studies), 2020)
Contemporary Nigeria has witnessed monumental rise in crime wave and in the quest to stem the tide, government has adopted various security policies to secure the lives and property of its citizens in the past, but none of these policies have actually yielded positive results. Human abduction, armed robbery, terrorism, bomb attacks and lots more have been the order of the day in the Country. The study seeks to ascertain the impact of closed circuit television (CCTV) cameras in Abuja metropolis. Six research questions and two hypotheses were formulated to guide the study, related literatures were adequately reviewed. A population of size of 900 was selected out of which a sample size of 300 respondents, which cut across all walks of life, participated in the study. Structured questionnaire was designed and used as instrument for data collection. Data collected were analyzed using direct interpretation of results gotten from respondents. Findings of the research revealed significant relationship between closed circuit television cameras and theory of deterrence, criminal justice, fear of crime, legality, policy formation and regulation of closed circuit television (CCTV). The development of software that can be integrated with the CCTV to display a person’s bio-data on the monitor when captured by the CCTV camera is among other recommendations for further research study.